Assessment of peripheral nervous system alterations in patients with the Fabry telated GLA-variant p.A143T - Godel, Tim; Cossel, Katharina von; Friedrich, Reinhard E.; Glatzel, Markus; Canaan-Kühl, Sima; Duning, Thomas; Kronlage, Moritz; Heiland, Sabine; Bendszus, Martin; Muschol, Nicole; Mautner, Victor-Felix (Diagnostics, 2020)
The purpose of this study is to examine alterations of the peripheral nervous system (PNS) in oligo-symptomatic patients carrying the Fabry related GLA-gene variant p.A143T by Magnetic Resonance Neurography (MRN) and skin biopsy. This prospective study assessed dorsal root ganglia (DRG) volume L3 to S2, vascular permeability of the DRG L5, S1, and the spinal nerve L5 in five patients carrying p.A143T in comparison to patients with classical Fabry mutations and healthy controls. Moreover, skin punch biopsies above the lateral malleolus of the right foot were obtained in four patients and intraepidermal nerve fiber density (IENFD) was counted individually. Compared to controls, DRG volumes of p.A143T patients were enlarged by 30% (L3, p < 0.05), 35% (L4, p < 0.05), 29% (L5, p = 0.15), 36% (S1, p < 0.01), and 18% (S2, p < 0.05), but less pronounced compared to patients carrying a classical Fabry mutation. Compared to healthy controls, vascular permeability was decreased by 40% (L5 right), 49% (L5 left), 48% (S1 right), and 49% (S1) (p < 0.01-p < 0.001), but non-significant less than patients carrying a classical Fabry mutation. Compared to sex-matched 5% lower normative reference values per decade, IENFD was decreased in three of four patients. MRN and determination of IENFD is able to detect early alteration of the PNS segment in oligo-symptomatic patients with the disease-modifying GLA-variant p.A143T on an individual basis. This procedure might also help in further GLA-variants of uncertain significance for early identification of patients with single major organ manifestation.